Urgensi Putusan Mahkamah Konstitusi Terhadap Penolakan Perkawinan Beda Agama Melalui Putusan Mahkamah Konstitusi Nomor 24/PUU-XX/2022 - Dian Amelia; Nanda Utama; Fadhilla Zulfa (LPPM Universitas Ekasakti Padang, 2023)
The existence of Article 36 of Law Number 23 of 2006 concerning Population Administration becomes a weapon for couples who wish to marry with different religions in registering their marriage through a decision from the District Court. This is contrary to Law Number 1 of 1974 concerning Marriage which prohibits interfaith marriages and also prohibits these marriages from being registered. In 2022 a citizen named E. Ramos Petege submitted a request for judicial review of Article 2 paragraph (1) and Article 8 letter F of Law Number 1 of 1974 concerning Marriage because these articles were considered to violate his constitutional rights. The Constitutional Court also decided to reject the petition of the applicant. Research using normative juridical method with the nature of descriptive analysis research. The results of this study explain that violations in the legal order of marriage in Indonesia are motivated by minimal understanding of religion with the assumption that marriage is only limited to civil relations and the Marriage Law does not explicitly imply a prohibition against interfaith marriages. Furthermore, the reasons for the District Court granting interfaith marriages are related to human rights in the 1945 Constitution and legal rules on population administration. So that the urgency of the decision of the Constitutional Court in rejecting interfaith marriages is to provide legal certainty and become a final and binding legal reference for all law enforcement agencies in Indonesia.